A meta‐analytic review of help giving and aggression from an attributional perspective: Contributions to a general theory of motivation - Rudolph, Udo; Roesch, Scott; Greitemeyer, Tobias; Weiner, Bernard (Cognition and emotion, 2004)
The present review syntheses 64 investigations on the determinants of helping and aggression involving more than 12,000 subjects, providing empirical tests of Weiner's (1986, 1995) theory of social conduct. A meta-analytic test of the proposed causal cognition-emotion-behaviour sequence reveals that judgements of responsibility determine the emotional reactions of anger and sympathy, and that these emotional reactions, in turn, directly influence help giving and aggression. Results are highly consistent across several potential moderator variables including type of culture, sample characteristics, publication year, and publication status. Moreover, the present analyses suggest that the hypothesised model holds true for real events as well as for simulated data. Exploratory comparisons between the helping versus the aggression domain suggest that comparable results are obtained for these two domains, except that perceptions of responsibility are more likely to exert an additional proximal role in aggressive retaliation as compared to help giving. The implications of these findings for a general theory of motivation in the interpersonal and the intrapersonal domains are discussed. (Original abstract)